Possible Persons and the Problems of Posterity. (1st May 1996) - Grey, William
Abstract : The moral status of future persons is problematic. It is often claimed that we should take the interests of the indefinite unborn very seriously, because they have a right to a decent life. It is also claimed (often by the same people) that we should allow unrestricted access to abortion, because the indefinite unborn have no rights. In this paper I argue that these intuitions are not in fact inconsistent. The aim is to provide an account of trans-temporal concern which resolves the prima facie inconsistency between commonly held intuitions about our obligations to future persons. I argue that our intuitions can be reconciled provided that we explicate obligations to the future in terms of impersonal principles subject to retroactive person-affecting constraints.